6(2z-1)-2(z+3)=3(z+1)

Simple and best practice solution for 6(2z-1)-2(z+3)=3(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2z-1)-2(z+3)=3(z+1) equation:


Simplifying
6(2z + -1) + -2(z + 3) = 3(z + 1)

Reorder the terms:
6(-1 + 2z) + -2(z + 3) = 3(z + 1)
(-1 * 6 + 2z * 6) + -2(z + 3) = 3(z + 1)
(-6 + 12z) + -2(z + 3) = 3(z + 1)

Reorder the terms:
-6 + 12z + -2(3 + z) = 3(z + 1)
-6 + 12z + (3 * -2 + z * -2) = 3(z + 1)
-6 + 12z + (-6 + -2z) = 3(z + 1)

Reorder the terms:
-6 + -6 + 12z + -2z = 3(z + 1)

Combine like terms: -6 + -6 = -12
-12 + 12z + -2z = 3(z + 1)

Combine like terms: 12z + -2z = 10z
-12 + 10z = 3(z + 1)

Reorder the terms:
-12 + 10z = 3(1 + z)
-12 + 10z = (1 * 3 + z * 3)
-12 + 10z = (3 + 3z)

Solving
-12 + 10z = 3 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-12 + 10z + -3z = 3 + 3z + -3z

Combine like terms: 10z + -3z = 7z
-12 + 7z = 3 + 3z + -3z

Combine like terms: 3z + -3z = 0
-12 + 7z = 3 + 0
-12 + 7z = 3

Add '12' to each side of the equation.
-12 + 12 + 7z = 3 + 12

Combine like terms: -12 + 12 = 0
0 + 7z = 3 + 12
7z = 3 + 12

Combine like terms: 3 + 12 = 15
7z = 15

Divide each side by '7'.
z = 2.142857143

Simplifying
z = 2.142857143

See similar equations:

| 20y-10=10 | | 3a*4a= | | b/14=5/10 | | X+(-4)+2x=14 | | 9-10x=77-38x | | -18x^2+65x+7=0 | | 3x^3-7x^2=-10 | | 9d-2d+6d-6=6d | | y/8=2/10 | | (3+5x^2)(3-5x^2)= | | 3x^3-7x^2=10 | | 9x-7=6x+16 | | (2x+3)2-3x-4=0 | | 16a^3b+4ab=0 | | 6+9+6= | | 12X^3+3X^2-24X^2-6X=0 | | (x+2)(x+8)=72 | | 5s+12=0 | | (3d^4-4d^3+6)(-3c^2d)= | | 12X^3+3X^2-24X-6X=0 | | -x^2+5x=3 | | (3d^4-4d^3+6)(-3cd)= | | 4(6X-5)2= | | 6d+3d-5d-8=2d | | 9n=8n+24 | | 3x-9=2x+15 | | 5(3x-2)5= | | 3n+10=70 | | 12n-3=9 | | 76-7x=38x+21 | | (3x-4)(x-4)(x+5)= | | 3n+6=3n |

Equations solver categories